Advanced research on the antioxidant and health benefit of elderberry (Sambucus nigra) in food – a review - Andrzej Sidor; Anna Gramza‐Michałowska (2014)
Elderberry plant (Sambucus nigra) is a good source of protein, free and conjugated forms of amino acids, unsaturated fatty acids, fibre fractions, vitamins, antioxidants and minerals. Analysis of elderberry showed that it contains high biological activity components, primarily polyphenols, mostly anthocyanins, flavonols, phenolic acids and proanthocyanidins, as well as terpenes and lectins. In folk medicine, elderberry has been used in the treatment of many diseases and ailments. Elderberry has medicinal properties associated with the presence of polyphenols, which are compounds with potential antioxidant properties. They can greatly affect the course of disease processes by counteracting oxidative stress, exerting beneficial effects on blood pressure, glycaemia reduction, immune system stimulation, antitumour potential, increase in the activity of antioxidant enzymes in the blood plasma, including also glutathione, and the reduction of uric acid levels.